The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1136/vr.115.19.488
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of bovine respiratory syncytial virus infection and clinical disease by vaccination

Abstract: A double blind field trial was carried out with a live attenuated bovine respiratory syncytial virus vaccine. The trial involved 530 calves, two to 10 months old, on 27 dairy farms, where respiratory problems due to bovine respiratory syncytial virus infections had been observed during the preceding year. In 17 herds either all calves were vaccinated (nine groups) or all calves received a placebo (eight groups). In 10 herds half the number of calves were vaccinated and the other half kept as non-vaccinated con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Field studies of early vaccination suggest that calves may be protected by either live or inactivated vaccines. In the Netherlands, Verhoeff and van Nieuwstadt (1984) gave calves two doses of vaccine before they were housed and challenged naturally, and observed a reduction of BRSV-associated disease. The calves were between two and 10 months of age when they were vaccinated but no data on the differences in the response or protection of calves with or without maternally derived antibody were given.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies of early vaccination suggest that calves may be protected by either live or inactivated vaccines. In the Netherlands, Verhoeff and van Nieuwstadt (1984) gave calves two doses of vaccine before they were housed and challenged naturally, and observed a reduction of BRSV-associated disease. The calves were between two and 10 months of age when they were vaccinated but no data on the differences in the response or protection of calves with or without maternally derived antibody were given.…”
Section: Discussionmentioning
confidence: 99%
“…Most such trials have been carried out in Europe; in one excellent example involving 530 calves on 27 farms, calves on farms where all calves were vaccinated with a modified live BRSV vaccine by intramuscular route had significantly decreased rates of BRSV infection and disease, compared to farms where calves were not vaccinated. Farms where half the calves were vaccinated had significantly decreased rates of disease but not infection (Verhoeff and van Nieuwstadt, 1984).…”
Section: Vaccines For Brsvmentioning
confidence: 94%
“…Because of the similarities between HRSV and BRSV, it should be possible to gain insight regarding factors that impact safety, efficacy, and duration of immunity in individuals vaccinated either in the presence or absence of circulating neutralizing antibodies using the BRSV model. Many published studies have shown that commercially available BRSV vaccines can induce protection against experimentally induced or naturally occurring BRSV disease (Durham and Hassard, 1990;Ellis et al, 2001;Van Donkersgoed et al, 1990b;Vangeel et al, 2007b;Verhoeff and van Nieuwstadt, 1984;West et al, 1999b;Xue et al, 2010).…”
Section: Vaccines For Brsvmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, only mild signs of upper respiratory tract disease were present in completely vaccinated groups following RSV infection. 61 In a recent study, an experimental inactivated RSV vaccine was compared with two live vaccines in a group of calves aged 4 to 8 months. 50 These calves had low or undetectable levels of maternal antibody to RSV.…”
Section: Vaccination Against Virusesmentioning
confidence: 99%